Tourists’ Revisit Intention to Beach Tourism Destinations in Bangladesh - Hasan, Md. Kamrul (Curtin University, 2019)
Coastal-based beach tourism is one of the least researched areas in tourism literature. This study aimed at examining tourists’ revisit intention to beach tourism destinations. Data were collected from 631 tourists who had visited beach destinations in Bangladesh. The results indicate that tourists’ revisit intention was directly influenced by destination image, tourists’ attitudes, satisfaction, PBC, and PSI. The findings contribute to the extension of body of knowledge in beach tourism settings.